Empire of the air : the men who made radio - Lewis, Tom, 1942- (Cornell University Press, 2021)
"Biography of 3 Americans, Lee de Forest, Howard Armstrong, and David Sarnoff, who turned a hobbyists' toy into radio, and launch the modern communications age. The narrative of their creations is punctuated by acts of idealism and imagination, greed and envy, ambition and determination--and genius. It covers 1899 to 1954"--